(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2021)
In the discourse of international law, the right to truth emerges as a new legal concept to mobilize a diversity of agendas and interests. The present study seeks to interpret the right to the truth as a right to memory from the analysis of the sentence of condemnation of Brazil by the Inter-American Court of Human Rights in the Gomes Lund et al. Case (“Araguaia Guerrilla”). As an exemplary case of petition before the Inter-American Court of Human Rights, it is sought to demonstrate that the persistent ignorance of the truth amounts to forced institutional amnesia and the persistence of crimes of forgetfulness which seek to erase the traces of past violence against the dignity of human person.